Enterprise financial performance under liquidity, solvency, and risk-based capital constraints - Sri Martina; Wico Jontarudi Tarigan; Ferdila Ferdila (International Journal of Enterprise Modelling, 2026)
Enterprise financial performance is a critical indicator of organizational sustainability, particularly in highly regulated and risk-sensitive industries such as insurance. Prior studies on insurance financial performance have largely emphasized profitability or macroeconomic determinants, while limited research has integrated liquidity, solvency, and risk-based capital (RBC) into a unified accounting-based framework at the enterprise level. Addressing this gap, this study investigates the financial performance effectiveness of a publicly listed Indonesian insurance company through an integrated assessment of liquidity, solvency, and regulatory capital adequacy. This research employs a quantitative descriptive approach using secondary data derived from audited annual financial statements of an insurance enterprise listed on the Indonesia Stock Exchange over the 2020–2023 period. Financial performance is evaluated using liquidity ratios (current ratio and cash ratio), solvency ratios (debt-to-assets ratio and debt-to-equity ratio), and the Risk-Based Capital ratio as a regulatory solvency benchmark. The findings reveal that the enterprise consistently maintains strong liquidity and capital adequacy above regulatory requirements, indicating effective short-term financial management and strong risk-absorption capacity. However, solvency analysis shows a relatively high reliance on debt financing, suggesting potential structural risks in long-term capital composition. This study contributes to enterprise modelling and accounting literature by proposing an integrated accounting-based framework that positions liquidity, solvency, and RBC as interrelated enterprise control mechanisms for evaluating financial performance effectiveness in regulated insurance institutions. The results provide practical implications for financial governance and regulatory compliance in emerging insurance markets. This study addresses the gap in prior insurance performance studies that examine liquidity, solvency, and capital adequacy separately by proposing an integrated accounting-based enterprise performance framework.